Integrating Organizational Justice and Affect: New Insights, Challenges, and Opportunities. - Hillebrandt, Annika; Barclay, Laurie J. (Social Justice Research, 2013)
Building on the foundation offered by Cropanzano et al. in their recent book titled (Cropanzano et al. in Social justice and the experience of emotions, Routledge, New York, 2011 ), we argue that further integrating the literatures on organizational justice and affect has the potential to create important insights that can further our understanding of both literatures. In order to capitalize on these opportunities, however, we argue that justice scholars must increase the clarity of our constructs, address critical gaps in the literature, and question underlying assumptions in the field as well as within the paradigms that have traditionally been adopted to explore justice issues. We propose a number of research avenues that can not only facilitate our understanding of organizational justice by addressing challenges and gaps in the literature, but can also help further integrate the organizational justice and affect literatures. We conclude by discussing methodologies and approaches that can help organizational justice researchers to explore these new research opportunities.